Evaluation of peroxidative stress of cancer cells in vitro by real-time quantification of volatile aldehydes in culture headspace - Shestivska, Violetta; Rutter, Abigail V; Sulé-Suso, Josep; Smith, David; Španěl, Patrik (Rapid communications in mass spectrometry, 2017)
RATIONALE: Peroxidation of lipids in cellular membranes results in the release of volatile organic compounds (VOCs), including saturated aldehydes. The real-time quantification of trace VOCs produced by cancer cells during peroxidative stress presents a new challenge to non-invasive clinical diagnostics, which as described here, we have met with some success. METHODS: A combination of selected ion flow tube mass spectrometry (SIFT-MS), a technique that allows rapid, reliable quantification of VOCs in humid air and liquid headspace, and electrochemistry to generate reactive oxygen species (ROS) in vitro has been used. Thus, VOCs present in the headspace of CALU-1 cancer cell line cultures exposed to ROS have been monitored and quantified in real time using SIFT-MS. RESULTS: The CALU-1 lung cancer cells were cultured in 3D collagen to mimic in vivo tissue. Real-time SIFT-MS analyses focused on the volatile aldehydes: propanal, butanal, pentanal, hexanal, heptanal and malondialdehyde (propanedial), that are expected to be products of cellular membrane peroxidation. All six aldehydes were identified in the culture headspace, each reaching peak concentrations during the time of exposure to ROS and eventually reducing as the reactants were depleted in the culture. Pentanal and hexanal were the most abundant, reaching concentrations of a few hundred parts-per-billion by volume, ppbv, in the culture headspace. CONCLUSIONS: The results of these experiments demonstrate that peroxidation of cancer cells in vitro can be monitored and evaluated by direct real-time analysis of the volatile aldehydes produced. The combination of adopted methodology potentially has value for the study of other types of VOCs that may be produced by cellular damage.
Keywords: Electrochemical Techniques; elektrochemické techniky; aldehydy; oxidace-redukce; oxidační stres; nádory; buněčné kultury; hmotnostní spektrometrie; nádorové buněčné linie; lidé; Oxidation-Reduction; Neoplasms; Oxidative Stress; Mass Spectrometry; Cell Line, Tumor; Humans; Aldehydes; Cell Culture Techniques